Estimating the Sea Current Field and Assessing the Potential for Exploiting Electricity from the Sea Current in the Estuary of the Mekong River - Thi Vui, Vu (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 1SDO - 10.25073/2588-1094/vnuees.4340, 2018)
Abstract: Exploiting renewable energy from the sea is a topic of great interest in recent years in Vietnam. Many coastal areas of our country have been surveyed to assess the potential of marine energy exploitation. However, there have been no studies detailing the potential of exploiting the sea current energy in the Mekong River mouth. This study aims to estimate the potential of marine power generation for the Mekong River mouth by calculating the ocean current flow using the Regional Ocean Modeling System (ROMS). It is estimated following one of the marine electricity generation equipment is being studied in Vietnam. The results show that the potential for power exploitation in the Mekong River mouth is positive, with total capacity reaching over 209 MWh at the river mouth, above 116 MWh in Con Dao in January and above 55 MWh in both locations in July in 2018. Keywords: Ocean currents, recycled energy, Mekong estuary, South East sea, ROMS. References: [1] Lê Đình Mầu, Nguyễn Bá Xuân, 2010, “Khái quát về năng lượng biển và bước đầu đánh giá tiềm năng của chúng tại Việt Nam”, Tuyển tập Nghiên cứu biển, XVII, tr. 199-206. [2] Doãn Mạnh Dũng, 2015, “Ý tưởng dùng dòng hải lưu để phát điện”, Báo khoa học Phổ thông số 50/14 (1652) ngày 2/1/2015 (được cập nhật ngày 16/01/2018 trên website kinhtebien.vn). [3] Pierrick Penven, Gildas Cambon, Thi-Anh Tan, Patrick Marchesiello and Laurent Debreu, 2010, ROMS AGRIF/ROMSTOOLS User’s Guide, Institut de Recherche pour le D´eveloppement (IRD), France. [4] Website: https://www.croco-ocean.org/